2011
DOI: 10.3892/ijmm.2011.831
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of conditionally replicating adenovirus and histone deacetylase inhibitors

Abstract: Abstract. Combination therapy of adenoviral gene therapy and a histone deacetylase (HDAC) inhibitor is important due to the enhancing effect of HDAC inhibitors on adenoviral transduction and transcription. However, contradictory results have been reported on the effect of combination of CRAd (conditionally replicating adenovirus) and HDAC inhibitors. This study was designed to investigate the interaction of CRAd and HDAC inhibitors and determine the ideal way to combine the two agents. Combination of HDAC inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Our findings demonstrated that both HDACi (SBHA and MS-275) pretreatment elevated CAR expression levels ( Figure 2 a) and membrane attachment of Ad to the surface of the cancer cell membrane ( Figure 2 b and Figure S5 ), in line with several other reports demonstrating that HDACi-treated cells show elevated CAR or αvβ3 integrin expression levels, that enhance cell internalization and transgene expression of Ad [ 23 , 38 , 39 , 40 ]. Importantly, our study was the first to demonstrate that HDACi treatments also elevated the expression levels of dynamin 2 and clathrin ( Figure S6 ), which are critical to clathrin-mediated endocytosis of Ad after Ad capsids are docked to CAR and integrin expressed on the cell surface [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings demonstrated that both HDACi (SBHA and MS-275) pretreatment elevated CAR expression levels ( Figure 2 a) and membrane attachment of Ad to the surface of the cancer cell membrane ( Figure 2 b and Figure S5 ), in line with several other reports demonstrating that HDACi-treated cells show elevated CAR or αvβ3 integrin expression levels, that enhance cell internalization and transgene expression of Ad [ 23 , 38 , 39 , 40 ]. Importantly, our study was the first to demonstrate that HDACi treatments also elevated the expression levels of dynamin 2 and clathrin ( Figure S6 ), which are critical to clathrin-mediated endocytosis of Ad after Ad capsids are docked to CAR and integrin expressed on the cell surface [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…[ 9 , 10 ] These drugs also affect non-histone targets including genes involved in cell cycle regulation, apoptosis and autophagy. [ 9 , 11 ] HDACi are reported to enhance oncolytic adenoviral therapy[ 12 ], however the effects of a panel of HDACi in patient-derived glioblastoma stem-like cells (GSC), a model that recapitulates the original tumor [ 13 ], have not been evaluated yet. Previous studies provide a rationale to systematically investigate the efficacy of HDACi as enhancers for Delta24-RGD in glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…Coxsackie adenovirus receptor (CAR) is the primary receptor for CVB3 to infect permissive cells. It was reported that HDACI increases the expression of CAR in several cancer cell lines ( 25 , 26 ). To investigate whether HDACI enhanced CVB3 replication by increasing CAR expression and CVB3 entry into cells, cardiac myocytes were treated with SAHA or TSA for various time periods, and CAR expression was determined by Western blotting.…”
Section: Resultsmentioning
confidence: 99%